Mapeamento do fluxo de valor: obstáculos, potencialidades e benefícios na cafeicultura - Carrijo, Pâmella Rodrigues Silva (Universidade Federal de São Carlos, 2021)
Lean Production has been standing out, especially in the industry, as a strategy to increase productivity. However, there is a great potential for the use of its tools and principles in other economic sectors, such as, for example, the agriculture and cattle raising sector. Aiming to contribute to the effort to explore this potential, this dissertation has as general objective to propose adaptations to the Value Stream Mapping tool (VSM) of the Lean Production System to the agricultural production, more specifically to the coffee culture. Therefore, a case study was conducted in a coffee producing farm, located in the southeast region of the country, aiming to collect the necessary data for the construction of maps adapted to the tool. The VSM tool was chosen through a systematic literature review, which identified and analyzed the use of the Lean Production System in agriculture, seeking to determine the tools used with greater recurrence in rural production. Based on the data collected with the case study, it was possible to identify obstacles, potentialities, and benefits of using the proposed tool. A graphic presentation of the Current and Future State Map proposed by the research was presented, as well as propositions that attempted to demonstrate how the tool can help reduce waste in the coffee culture. The adaptations proposed in this study aimed to adapt the tool to an agricultural context, resulting in a visual agricultural process mapping model which is easy to apply. The research concluded that the VSM tool can also be used in agriculture, more specifically in the coffee culture, as suggested in the literature.
Value stream mapping: obstacles, potentials and benefits in coffee production
Keywords: Mapeamento do fluxo de valor; Cafeicultura; Agricultura; Value stream mapping; Coffee production; Agriculture; Lean production; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO